(3eYQaI GdQLGd hLQMge hJYOjdges - (3CHh YHjO eMeO Hf Ydj Hf YKeGf GdCLQis; (3CHh HcQ eMeO Hf Ydj Hf YOj Hf Ydj Hf RNQ GdefbQjs
(3ChdgG (B:s
(3CNHQfG GdTjN GdChMO GdEeGe GdMGaX CHh WGgQ CMeO Hf eMeO Hf CMeO Hf eMeO EHQGgje GdSdai GdCUHgGfi hPcQ SajGf Uajf abGd eG COQi CNWChG Ce GUGHhG s
(3BNQgG (B:s
(3SCdJ CHG OGhO Yf HfOGQ hCMeO Hf SfGf abGd CMeO Hf SfGf bdJ dCHi OGhO YHjO Gddg GHf GdMSf YfOc MLI bGd cGf abgkG BNQ GdLRA GdKGdK ef GdCUd hChd GdQGHY efg hGdMeO ddg QH GdYGdejf s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3C UHMi GdSGeQGFi s
Keywords: (3GdMOjK h GdeUWdMs